Comparison of clear lens extraction and collamer lens implantation in high myopia - Ahmed M Emarah (Dove Medical Press, 2010)
Ahmed M Emarah, Mostafa A El-Helw, Hazem M YassinCairo University, Cairo, EgyptAim: To compare the outcomes of clear lens extraction and collamer lens implantation in high myopia.Patients and methods: Myopic patients younger than 40 years old with more than 12 diopters of myopia or who were not fit for laser-assisted in situ keratomileusis were included. Group 1 comprised patients undergoing clear lens extraction and Group 2 patients received the Visian implantable collamer lens. Outcome and complications were evaluated.Results: Postoperative best corrected visual acuity was -0.61 ± 0.18 in Group 1 and 0.79 ± 0.16 in Group 2. In Group 1, 71.4% achieved a postoperative uncorrected visual acuity better than the preoperative best corrected visual acuity, while only 51.8% patients achieved this in Group 2. Intraocular pressure decreased by 12.55% in Group 1, and increased by 15.11% in Group 2. Corneal endothelial cell density decreased by 4.47% in Group 1 and decreased by 5.67% in Group 2. Posterior capsule opacification occurred in Group 1. In Group 2, lens opacification occurred in 11.11%, significant pigment dispersion in 3.7%, and pupillary block glaucoma in 3.7%.Conclusion: Clear lens extraction presents less of a financial load up front, and less likelihood of the need for a secondary intervention in the future. Clear lens extraction is a more viable solution in developing countries with limited financial resources.Keywords: clear lens extraction, implantable collamer lens, myopia